Application of a composite ultrafiltration membrane for biodiesel purification - Rodriguez, Natalia Evelin (2018)
This study was carried out to investigate the potentialities of the application of membrane technology in biodiesel purification without need of the decantation step. A new composite UF membrane was prepared from poly(vinylidene fluoride) casting solution (17 wt%) containing a sulfonated Carbon (20 wt%). The assays were performed in a dead-end filtration cell with synthetic mixtures of the transesterification reaction products. The influence of two operational variables was analyzed, transmembrane pressure (ΔP = 4-8 bar) and temperature (T = 50-60°C). The membrane performance was evaluated determining the flux and the permeate compositions. Temperature resulted to be the most important operational variable. An increase in 10°C duplicated the permeate flux at 6 and 8 bar. The best performance was obtained at 60°C and 8 bar, with a flux of 12.6 Lm-2h-1. In this operative conditions, the influence of the added acidified water (Wadd = 0-20 %v/v) in the synthetic mixture was evaluated, which increased considerably permeate fluxes. Finally, the impact of synthetic mixture composition was determined for the assayed best operational conditions. The higher flux value was measured in the mixture with less glycerol and without soaps. In all assays the biodiesel retention was complete and the permeates were composed mainly of glycerol and ethanol.